Exploring the Influence of Internet Usage on Religious Moderation: A Phenomenological Study Among Gen Z - Jamaludin, Nur; Choirin, Muhammad; Bin Aini, Zulkefli; Anam, Moh Khoirul (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2024)
The rapid advancement of the internet has significantly influenced how Generation Z engages with religious knowledge and practices, raising concerns about its impact on their perspectives, attitudes, and behaviors regarding religious moderation. This study aims to examine this influence, focusing on actively enrolled students who demonstrate internet addiction and rely heavily on online platforms for religious activities. Employing a qualitative phenomenological approach, data were gathered through in-depth interviews and observations to capture the lived experiences of these students. Findings reveal that most students spend over seven hours daily online, making the internet a primary source of academic and religious knowledge. This extensive use shapes their understanding of Islamic principles and their attitudes toward religious moderation, with online platforms perceived as convenient and reliable for accessing religious content. However, the study highlights the need for supervision and guidance to foster critical thinking and discernment, emphasizing the importance of digital literacy in promoting balanced and thoughtful religious perspectives among Generation Z in the digital era